Complex horseshoe fistula-in-ano in a child - Apak, Sami; Kazez, Ahmet (My University, 2002)
Horseshoe fistula-in-ano is very rare in children. It is derived from and abscess which is located in the deep posterior anal space and develops fistulae to the gluteal region and sacrum. It is characterised by multiple fistula which are for from the anus and requires a more complex treatment than the classical fistula-in-ano. A 3 year old girl with horseshae fistula-in-ano was treated by posterior saggital anorectoplasty following a colostomy. The was no recurrence at one year follow-up. We suggest fistulectomy with posterior sagital approach in this rare and complex pathology in childhood.
Çocukta kompleks atnali anal fistül
Keywords: Child; Fistula-in-ano; Horseshoe fistula; Posterior sagittal approach